Ultra-Short Pulses With High Repetition Frequency in Transmission Plasmonic Systems - Shilei Li; Yanan Qi; Liming Li; Dan Yu; Benyi Wang (IEEE Photonics Journal)
Ultra-short pulses with high repetition frequency have great application prospects in the field of nano-optics. Here, in the case of continuous wave incidence, the femtosecond pulses with THz repetition frequency are achieved in the transmission system consisting of quantum emitters (QEs) and plasmonic resonators. The generation mechanism of the ultra-short pulses with high repetition frequency is elucidated by semi-classical model. Attribute to the presence of the two-level QEs, the field amplitude in plasmonic resonator is oscillating with time, resulting in the transmittance of the system behave as the form of pulse oscillation. Moreover, the pulse repetition frequency and extinction ratio can be freely controlled by the incident light intensity and QEs number density to obtain the required ultra-short pulses at nanoscale. This also has potential applications in high-speed signal processing fields and generating optical clock signals that can be used in optical computing.